A Novel Mixed-Mode CCII-Based Filter - Muhammad Taher Abuelma'atti; Abdulwahab Bentrcia (Active and Passive Electronic Components)
A new mixed-mode biquad circuit is presented. The circuit uses five second-generation current conveyors, seven resistors, and two grounded capacitors and can realize lowpass, highpass, bandpass , notch, lowpass notch, highpass notch and allpass responses from the same topology. The circuit can be driven by voltage or current and its output can be voltage or current. The parameters ωo and ωo/Qo enjoy independent electronic tunability. Simulation results are included.